Restructuring proposal for the production and service area of the Jonathan dining room in the community of Ayangue-Santa Elena. - Zamora Flores, Fátima Gabriela; Parrales Hernández, Cristian Alejandro (Ingeniería Química y Desarrollo, 2024)
The commune of Ayangue is a horseshoe-shaped family resort, it is a town of few inhabitants with fishing activities and crafts. Currently it is inhabited by both local and foreign people, the high season is the coast that runs from January to April and the saw season is in the months from June to August. The Jonathan dining room has been in operation for more than 30 years providing the national tourist as a foreigner with the typical cuisine of the seafood-based sector. The Jonathan dining room shows a lack of organization within the facilities, so it has generated problems in the distribution of space in production and service, in addition, the establishment staff does not have fundamental training as they are to offer a good service. The methodology used in this work is the mixture with the objective of not only collecting bibliographic information, but also visiting the establishment to apply the techniques of observation, interviews, and surveys to know the conditions in which it is found. To determine the respective improvements to the problem of the establishment, applying the techniques of observation, surveys, interviews to the clients and the personnel of the establishment. The improvements that are proposed and their implementation based on the data collected will serve to improve the attention as the income of the premises.